SEC-seq: association of molecular signatures with antibody secretion in thousands of single human plasma cells - Rene Yu-Hong Cheng; Joseph de Rutte; Cade Ellis K. Ito; Andee R. Ott; Lucie Bosler; Wei-Ying Kuo; Jesse Liang; Brian E. Hall; David J. Rawlings; Dino Di Carlo; Richard G. James (Nature Communications)
Abstract The secreted products of cells drive many functions in vivo; however, methods to link this functional information to surface markers and transcriptomes have been lacking. By accumulating secretions close to secreting cells held within cavity-containing hydrogel nanovials, we demonstrate workflows to analyze the amount of IgG secreted from single human B cells and link this information to surface markers and transcriptomes from the same cells. Measurements using flow cytometry and imaging flow cytometry corroborate the association between IgG secretion and CD38/CD138. By using oligonucleotide-labeled antibodies we find that upregulation of pathways for protein localization to the endoplasmic reticulum and mitochondrial oxidative phosphorylation are most associated with high IgG secretion, and uncover surrogate plasma cell surface markers (e.g., CD59) defined by the ability to secrete IgG. Altogether, this method links quantity of secretion with single-cell sequencing (SEC-seq) and enables researchers to fully explore the links between genome and function, laying the foundation for discoveries in immunology, stem cell biology, and beyond.